SIX SIGMA IMPLEMENTATION IN INDONESIA INDUSTRIES AND BUSINESSES: A SYSTEMATIC LITERATURE REVIEW - Widjajanto, Sugiri; Purba, Humiras Hardi (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
Understanding quality in manufacturing starts with defect identification and improvement finding. Reliability that influenced by equipment design or working methods or environment has led to concept of improvement with six sigma method and this has been absorbed in Indonesia industries as well. This article discusses about six sigma implementation in Indonesia from various business and industries. The method is to review research articles that are published within 2016-2020 with keyword DMAIC and six sigma. The results from 52 selected articles is obtained average 3.68 sigma value of Indonesia industries within year 2016-2020 with the least value 1.10 from crude palm oil refinery and the highest is 5.10 from bagging process of sugar refinery. However, six sigma application is not always satisfying  concerning its suitability function, requirement of industries, culture, local regulation, and internal business concern, especially in terms of efficiency and cost. Future research is suggested utilizing industry 4.0 concept to enhance six sigma implementations.